Cloning of adp-glucose pyrophosphorylase involves in starch biosynthesis pathway in sago palm - Dayang Suziana, binti Mawi. (Universiti Malaysia Sarawak, (UNIMAS), 2004)
The main objective in this study is to clone ADP-glucose pyrophosphorylase, which is a gene that involves in starch biosynthesis pathway. In order to accomplish this objectives, three main steps which are the isolation of sago genomic DNA, Polymerase Chain Reaction and cloning putative ADP-glucose Pyrophosphorylase need to be done. The first two steps had been done but unfortunately the last step could not be proceed due to the failure to obtain any PCR product.